Pengaruh Harga, Selera, Kualitas Produk, dan Lokasi terhadap Permintaan pada Konsumen Hot Pangsit Bar-Bar di Kota Jambi - M Rizieq Alfarizi; Sissah Sissah; Sri Rahma (Lembaga Yasin AlSys, 2025)
The intense competition in the culinary industry in Jambi City, including in the snack food sector such as Hot Pangsit Bar-Bar, necessitates a comprehensive understanding of the factors influencing consumer purchasing decisions. This study aims to analyze the influence of price, taste, product quality, and location on consumer demand for Hot Pangsit Bar-Bar, both partially and simultaneously. A quantitative research method with a survey approach was used by distributing questionnaires to 100 active consumers. Data analysis was conducted using multiple linear regression to examine the relationships among variables. The results show that all four variables, price, taste, product quality, and location have a positive and significant partial effect on demand, and a simultaneous significant effect with a significance value of 0.000 (p < 0.05). The Adjusted R Square value of 0.555 indicates that 55.5% of the variation in consumer demand can be explained by these variables. The study concludes that marketing strategies that emphasize competitive pricing, alignment with consumer taste preferences, consistent product quality, and strategic location are crucial for increasing consumer demand. These findings offer practical implications for culinary business owners to optimize key factors in attracting and retaining customers.